Modern treatment of appendicitis - Stevenson, W. Sinclair (The University of Edinburgh, 1910)
Appendicitis is a disease which has only very recently - within the last twenty years - been studied at all. The pathology of the disease shows us that it occurs in attacks of three kinds - acute, medium, and very mild. In the acute variety the disease is well under - stood and the treatment is acknowledged by everyone to be immediate operative interference. In the mild variety, the symptoms are so slight that the disease cannot be definitely recognised. Nevertheless pathological changes occur in the appendix which produce serious results later on. In the medium variety, the symptoms are definite but the treatment varies. Appendicectomy during the height of a first attar is a perfectly safe operation, as well as a simple one. Appendicectomy during the quiescent period after an attack is no safer, and is far more liable to be a difficult operation. Convalescence is prolonged. The expectant treatment of a medium attack is unsafe and unreliable. Further attacks are almost certain to occur, and operation is called for in the long run - but the operation after several attacks is attended by difficulties and dangers which are not present in an operation during the first attack. The questions set down in the Preface may therefore be answered thus: - Definite recognisable appendicitis should be transferred entirely to the domain of surgery. Appendicectomy should not however be left to the specialist. When done at the right time it is a simple operation which can and should be performed by every medical ractitioner. Appendicitis should always be treated surgically except under circumstances where extraneous considerations make the operation a greater risk than the disase. The present mortality of the disease could be firiensely reduced were all cases operated on as soon as he condition was diagnosed. Under these circumstances he mortality should not exceed 2 -3 per cent. The resent mortality of the disease being from 7 to 10 er cent in all cases. The one rule of treatment should be that directly appendicitis is diagnosed, an operation should be performed at the earliest possible moment.